Flipbook-Based Digital Reading Corner as a Strategy to Improve Creative Reading Ability and Students’ Literacy Creativity in Junior High School - Saidah, Elisa; Rido Andhi Yaksa; Niswatul Istiana Puji Syafitri; Kholifatus Ibramovic; Trinil Dwi Turistiani (The Future of Education Journal, 2026)
The low level of creative reading ability and literacy creativity among junior high school (SMP) students is a fundamental problem in Indonesian Language learning. PISA 2022 data placed Indonesia at 69th out of 81 countries with a reading score of 359, well below the OECD average of 476. Meanwhile, conventional reading corners (pojok baca), as the main instrument of the School Literacy Movement (GLS), are considered suboptimal due to limited collections, low interest among digital-native students, and the absence of interactive approaches. This study aims to analyze the characteristics of digital flipbooks as literacy media, identify the limitations of conventional reading corners, design a flipbook-based digital reading corner model, and describe its implementation at the junior high school level. The method used is a library research approach with content analysis of 15 accredited journal articles published between 2021–2025. The results show that digital flipbooks have multimodal, interactive, and flexible characteristics relevant to Generation Z's learning styles. The designed flipbook-based digital reading corner model includes four components: digital content curation, reading day sessions, creative reflection, and digital literacy portfolios. Implementation of this model in Grade VIII Indonesian Language learning significantly improved student engagement and creative reading ability. These findings confirm that integrating flipbooks into a digital reading corner ecosystem is an adaptive and sustainable literacy strategy in the digital era.